2002
DOI: 10.1124/jpet.102.040378
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of Neurokinin-1 Receptor Resensitization

Abstract: Prolonged or repeated activation of many G protein-coupled receptors induces rapid desensitization followed by a period during which receptors are resensitized. In this study, concanavalin A (Con A) and monensin were used to investigate the mechanisms of desensitization and resensitization of the neurokinin-1 receptor. Con A inhibits internalization, whereas monensin prevents receptor recycling. The effects of Con A and monensin on desensitization, resensitization, receptor phosphorylation, endocytosis, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 15 publications
(23 reference statements)
2
16
0
Order By: Relevance
“…These results may suggest that alternative mechanisms to receptor internalization exist in the process of receptor resensitization. Indeed, a recent study with desensitized neurokinin-1 receptors identified a receptor resensitization that occurred before receptor recycling (34), consistent with the findings described here.…”
Section: Fig 7 Serine 369 Dephosphorylation Of the Agonist-incubatesupporting
confidence: 90%
“…These results may suggest that alternative mechanisms to receptor internalization exist in the process of receptor resensitization. Indeed, a recent study with desensitized neurokinin-1 receptors identified a receptor resensitization that occurred before receptor recycling (34), consistent with the findings described here.…”
Section: Fig 7 Serine 369 Dephosphorylation Of the Agonist-incubatesupporting
confidence: 90%
“…Thus, the cells experienced four solution changes over a period of at least 30 min before the radioligand was added. Since the dissociation rate constant of substance P is 0.28 min Ϫ1 (Takeda et al,1992), the unlabeled substance P should have been removed during the washes, and the solution changes prior to the addition of radiolabeled substance P. We confirmed the effectiveness of these steps to remove unlabeled substance P in previous experiments (Bennett et al, 2002).…”
Section: Casupporting
confidence: 75%
“…While studying the effects of monensin and concanavalin A on rNK1R desensitization, internalization, recycling, and resensitization, we found that, following agonist-induced rNK1R desensitization and internalization, there was an increase in rNK1R-mediated Ca 2ϩ signaling following a 60-min recovery period without agonist, but there was not an equivalent return of plasma membrane receptor binding during the same recovery period (Bennett et al, 2002). Using a fluorescent substance P analog, we also showed that internalization corresponds with a decrease in plasma membrane binding of radiolabeled substance P following receptor activation, and recycling corresponds with an increase in binding following internalization.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…This sequence could result in a blockade of signaling without internalization, however, the binding of arrestin to the ligand/receptor complex is thought to proceed to endocytosis via clathrin-coated pits (Law and Loh, 1999;Ferguson, 2001;von Zastrow et al, 2003). The separation of internalization and desensitization has been reported for other G-protein-coupled receptors such as ␤ 2 -adrenergic and neurokinin-1 receptors (Pippig et al, 1995;Bennett et al, 2002), but it has also been show that the desensitization of somatostatin and V1b vasopressin receptors requires internalization (Beaumont et al, 1998;Hassan and Mason, 2005). Although this sequence has been established in many heterologous systems, the role of this process in MOR signaling is the subject of some debate.…”
Section: Desensitization and Receptor Traffickingmentioning
confidence: 94%